2011
DOI: 10.1111/j.1466-7657.2011.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in job strain among American and immigrant long‐term care workers

Abstract: Background Nursing homes are occupational settings, with an increasing minority and immigrant workforce where several psychosocial stressors intersect. Aim To examine racial/ethnic differences in job strain between Black (n=127) and White (n=110) immigrant and American direct-care workers at nursing homes (total n=237). Methods Cross-sectional study with data collected at four nursing homes in Massachusetts, during 2006-2007. We contrasted Black and White workers within higher-skilled occupations such as R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 35 publications
(63 reference statements)
1
57
0
5
Order By: Relevance
“…Disparities in the workplace psychosocial environment, including low job control and high job strain, have previously been reported and are generally found to be greater in Black subjects when contrasted with Whites or Latinos [Quinn et al, 2007;Meyer et al, 2011;Hurtado et al, 2012;Meyer and Mutambudzi, 2012]. While the effects of low job control and high strain, including hypertension, cardiovascular disease, and adverse pregnancy outcomes are well described [Karasek, 1996;Landsbergis and Hatch, 1996;de Lange et al, 2003;Landsbergis et al, 2003;Meyer et al, 2007;Smith et al, 2008a,b], the underlying reasons for disproportionately high adverse work exposures in Blacks has received less attention.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Disparities in the workplace psychosocial environment, including low job control and high job strain, have previously been reported and are generally found to be greater in Black subjects when contrasted with Whites or Latinos [Quinn et al, 2007;Meyer et al, 2011;Hurtado et al, 2012;Meyer and Mutambudzi, 2012]. While the effects of low job control and high strain, including hypertension, cardiovascular disease, and adverse pregnancy outcomes are well described [Karasek, 1996;Landsbergis and Hatch, 1996;de Lange et al, 2003;Landsbergis et al, 2003;Meyer et al, 2007;Smith et al, 2008a,b], the underlying reasons for disproportionately high adverse work exposures in Blacks has received less attention.…”
Section: Discussionmentioning
confidence: 91%
“…A fivefold difference is apparent between Black and White participants. While the health effects of racial discrimination have been well-described [Curtis et al, 1997;Williams et al, 1997;DinDzietham et al, 2004;Hurtado et al, 2012], this pathway appears to obviate the effect of education on health entirely in Blacks, and thus may provide at least a partial explanation for decreasing returns in health from increased education that have been described in African-Americans for over two decades [McGrady et al, 1992;Collins and Butler, 1997;Collins et al, 2004;Farmer and Ferraro, 2005;Meyer et al, 2010].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent systematic reviews suggest that work stress-related cardiovascular risk is more consistently observed in male samples than in women (Backe, Seidler, Latza, Rossnagel, & Schumann, 2012) whereas marital stress is more important for women (Orth-Gomer, et al, 2000). For sleep, socioeconomic conditions related to neighborhood and other family factors as well as overall job insecurity could well shape patterns of risk of short sleep duration for many people in lower socioeconomic positions (Bartley, 2005; Bartley & Ferrie, 2001; Beatty et al, 2011; Ertel, Berkman, & Buxton, 2011; Hurtado, Sabbath, Ertel, Buxton, & Berkman, 2012; Okechukwu, El Ayadi, Tamers, Sabbath, & Berkman, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Beschäftigte mit Migrationshintergrund sind allgemein häufig, aufgrund mangelnder Deutschkenntnisse, geringer Qualifikation oder fehlender Anerkennung von ausländischen Abschlüssen, als An-und Ungelernte beschäftigt [6,17]. In der Studie von Hurtado et al [26] berichteten Pflegeassistenten mit Migrationshintergrund häufiger über arbeitsplatzbezogene Beanspruchung und geringere Einflussmöglichkeiten als die nichtmigrierten Beschäftigten. Giver et al [19] [39], das "DemandControl-Model" (DCM) [27] und das "Demand-Control-Resources-Model" (DCR) [36].…”
Section: Introductionunclassified